2007
DOI: 10.1021/jf0624289
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions, Solubility, and Crystallization Kinetics of Phytosterols and Phytosterol−Oil Blends

Abstract: The thermal properties, solubility characteristics, and crystallization kinetics of four commercial phytosterol preparations (soy and wood sterols and stanols) and their blends with corn oil were examined. Differential scanning calorimetry (DSC) revealed narrow melting peaks between 138 and 145 degrees C for all phytosterol samples, reversible on rescan. Broader and less symmetrical melting transitions at lower temperatures with increasing oil content were observed for two samples of phytosterol-oil admixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 25 publications
11
63
0
1
Order By: Relevance
“…Yet, sterols and mixtures of sterols/stanols have higher solubility than stanols alone. Among these, wood stanols were slightly better solubilised in one study than their soya counterparts (Vaikousi et al 2007). The addition of water to oil tends to decrease phytosterol solubility by twofold (Christiansen et al 2002).…”
Section: Solubilitymentioning
confidence: 94%
See 2 more Smart Citations
“…Yet, sterols and mixtures of sterols/stanols have higher solubility than stanols alone. Among these, wood stanols were slightly better solubilised in one study than their soya counterparts (Vaikousi et al 2007). The addition of water to oil tends to decrease phytosterol solubility by twofold (Christiansen et al 2002).…”
Section: Solubilitymentioning
confidence: 94%
“…Enova oil marketed by ADM). The partially polar nature of phytosterols, due to the presence of hydroxyl group, may account for this (Vaikousi et al 2007).…”
Section: Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Observing all other blends, the presence of FP, in general terms, did not modify their crystallization profile. The low effect on crystallization profile of these blends is due to the high melting point of FP, about 140 °C for FP, and their low solubility in fatty systems, 2 -5% (25 -50 °C) in corn oil, according to data reported by Vaikousi et al, 2007. Once the solubilized FP co-crystallize with triacylglycerols, and they are mainly responsible for the modification of the crystallization behavior of the systems. In these blends, a great fraction of these compounds was probably not solubilized, thus causing little effect on the thermal behavior of the fatty mixtures.…”
Section: Thermal Behaviormentioning
confidence: 89%
“…It was also observed for these blends a X-ray diffraction peak at 2θ of about 15.02° representing the crystal arrangement of the FP molecules. Vaikousi et al, 2007 reported X-ray diffraction lines related to FP at 2θ of 4. 6, 6.9, 9.35, 11.7, 14.85, 16.5, 18.4 and 21.9°.…”
Section: Polymorphismmentioning
confidence: 99%